Variabilidade morfossedimentar das praias estuarinas de Caripi e Itupanema ( Barcarena, Pará ) - SALDANHA, Diego Silva (2019)
The beaches are very sensible and dynamic environments and suffer permanent influence from meteo-oceanographical and antropical processes, being this responsible for the morphossedimentary changes. The morphossedimentar variability studies about beach environments allow to identify higher or lower places and periods of erosion and deposition in the beach environment. The Caripi and Itupanema estuarine sandy beaches are located in the Barcarena city (PA) and are under the influence of a two well defined climate periods: dry (June to November) and wet (December to May). The Caripi and Itupanema estuarine beaches are seated on the holocenics sediments of the Grupo Barreiras. For the beach morphology and the sedimentology survey, had been carried transversal profiles to the shoreline in two profiles in Caripi and Itupanema beaches in two field stages: February (wet) and November (dry). The results shows a relative morphossedimentar variability beach, where, the Caripi beach presented Reflective, Low Tide Terrace and Ultradissipative classification beach in the dry period. On Itupanema beach the values are for Reflective, Low Tide Terrace and Dissipative beaches.